Periodontal damage after thermal inhalation injury — The impact of high temperature inhalation injury on long term periodontal health. Issue 4 (June 2022) - Schappacher, Robert; Rapp, Matthias; Muth, Claus-Martin; Nölke, Jan; Amrehn, Lance; Liener, Ulrich; Bökeler, Ulf; Orth, Matthias; Fillies, Thomas
Highlights: We report a correlation between a thermal inhalation injury and periodontitis. Oral-health related quality of life is reduced in patients after inhalation injury. Inhalation injury is the strongest moderator for periodontitis in our findings. Abstract: Purpose: Thermal inhalation injury is a common, life-threatening problem in burned patients. Whether or not this single event of damage to the oral integrity causes long term health problems is yet to be examined. Material and methods: All consecutive burn patients between 2014 and 2017 of Marienhospital Stuttgart (MHS), Germany, with at least 10% of burned skin surface were included and compared. The Periodontal Screening Index as well as Vitamin D levels were examined. Vitamin D has been suspected to contribute to the genesis of periodontitis . Risk factors and subjective oral life quality were prompted. Results: We included a total of 32 patients, 15 of which had an inhalation injury in their medical history. Risk factors were examined via Renatus' questionnaire. While risk factors were equally distributed in both groups we saw a remarkable difference in periodontal integrity, with the Periodontal Screening Index (PSI) per sextant differing drastically (with inhalation injury: 2.40, without inhalation injury: 1.10, p < 0.001). Patients with an inhalation injury had a mean of 5.2 out of 6 possible sextants with a pathologic PSI (with the median being 6/6), while patients without an inhalation injury had a mean of 1.83 out of 6 (median: 1/6), p < 0.001. The oral health impact profile showed a difference as well, albeit without statistical significance (with inhalation injury: median = 11, without: median = 3.5, p = 0.414). A correlation between Serum Vitamin D levels and periodontal integrity could not be seen in this group. Conclusion: Inhalation injury is a possible cause for periodontitis and hence impacts the quality of life of burned patients.